Value of 18-fluoro-deoxyglucose positron emission tomography with computed tomography in comparison to multi-slice computed tomography in recurrent bladder cancer - Veljković, Miloš; Beatovic, Slobodanka; Grozdic-Milojevic, Isidora; Petrovic, Jelena; Odalovic, Strahinja; Stojiljkovic, Milica; Artiko, Vera; Sobic, Dragana (Medical Research, 2023)
AbstractIntroduction: Positron emission tomography with computed tomography using 18-fluoro-deoxyglucose (18FDG-PET/CT) is still not used routinely in clinical practice for the evaluation of recurrent bladder cancer. Recent guidelines recognize the importance of 18FDG-PET/CT, but multi-slice computed tomography (MSCT) is still recommended for monitoring these patients. Aim: To determine the agreement between 18FDG-PET/CT and MSCT findings in the categorization of patients in N and M stages of the disease, as well as the agreement of two diagnostic modalities in the number of detected lesions.Material and methods: 31 patients (22 men and 9 women), mean age 61.2 ± 9.2 years, were included in our study after surgical treatment and histopathological confirmation of bladder cancer. Zones of pathological uptake of 18FDG were interpreted visually and semi-quantitatively using the maximum standardized uptake value (SUVmax). The agreement of 18FDG-PET/CT findings was compared to previous MSCT using Cohen’s kappa test for interobserver agreement, interpreted based on the Altman’s criteria.Results: The overall agreement between 18FDG-PET/CT and MSCT in N stage of the disease was 77% (κ = 0.54; moderate agreement); in stage N0 68%, N2 77%, N3 29%. In M stage, total agreement was 53% (κ = 0.10; poor agreement); in stage M0 39%, M1a 22%,  M1b 44%. 18FDG-PET/CT detected a total of 29 lesions in N stage of the disease, while MSCT detected 16 lesions, with the agreement of 71% (κ = 0.41; moderate agreement). In the M stage of the disease, 18FDG-PET/CT detected 42 lesions and MSCT detected 30 lesions, with overall agreement of 52% (κ = 0.07; poor agreement).Conclusion: Our results show that there is a moderate agreement between 18FDG-PET/CT and MSCT findings in the categorization of patients and number of detected lesions in N stage of disease, but that 18FDG-PET/CT detects more lesions. 18FDG-PET/CT also detects a higher number of lesions in stage M disease, but agreement with MSCT findings is poor.
Keywords: recurrent bladder cancer; PET/CT; MSCT